Performance Comparison of Single and Two-Phase Biogas Digesters Treating Dairy Cattle Manure at Tropical Ambient Temperature - S. Sutaryo; A. N. Sempana; C. M. S. Lestari; A. J. Ward (Tropical Animal Science Journal, 2020)
The biodegradation process of organic waste in anaerobic digestion can be in a single or two-phase bio-reactor. This study examined the effect of different biogas digester configurations (single and two-phase) on methane production of dairy cattle manure (DCM) at tropical ambient temperature. Three identical reactors were used in this study (R1, R2, and R3). The two-phase digesters consisted of reactors R1 and R2. R1 had a 2.1 L working volume and 3 d hydraulic retention time (HRT), while R2 had 5.25 L working volume and 22 d HRT (R1 and R2 had a 25 d HRT). The digested slurry of R1 was used to feed R2. R3 served as the single-phase digester and had 5.25 L working volume and 25 d HRT. Methane production were 14.31, 132.82, and 146 L/kg VS for R1, R2, and R3, respectively. The results showed that there was no positive effect of the application of a two-phase digester configuration on the specific methane yield of DCM per kg volatile solids added than that in the single-reactor. Methane production was detected in the first reactor of the two-phase digester configuration and the total methane production of the two-phase digester was found to be 29.98% higher (p<0.05) than that of the single reactor in terms of digester volume (0.41 VS 0.31 L/L/d). Both digester configurations performed well, indicated by a stable methane production and low volatile fatty acids and total ammonia concentrations. The two-phase bio-digester configuration can significantly increase methane production in terms of digester volume.